STRATEGI DINAS PARIWISATA DAN KEBUDAYAAN DALAM PENGEMBANGAN PENUNJANG DESTINASI PARIWISATA BERBASIS GEOPARK DI GEOSITE BATU KASAH KABUPATEN NATUNA TAHUN 2019-2020 - Rohman, Ainur; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Tourism development in Natuna is an interesting phenomenon to discuss, this is because in 2015-2018 the Natuna tourism sector had a number of tourist visits that did not show significant development. However, in 2019, after the establishment of Natuna Regency as a National Geopark site, the number of tourist visits showed significant tourist visits. With the increase in the number of tourists since the establishment of Natuna Regency as a National Geopark area, this is certainly a question whether the strategy of the Natuna Regency Department of Tourism and Culture can be said to be successful in developing tourism in the area. This type of research is descriptive. The research location is the office of the Natuna Regency Department of Tourism and Culture as the main actor in the development of the Batu Kasah Geosite in Natuna Regency and direct observation to the Batu Kasah Geosite location. Data was collected through purposive sampling informants. Data collection techniques using interviews, documentation and observation. The results of the study concluded that the Natuna Regency Department of Tourism and Culture in its government strategy formulates at least five things that are the focus in tourism development at Batu Kasah Geosite, that is: Tourism product development strategy, marketing strategy, accessibility development strategy, infrastructure development strategy and business development strategy. The strategy carried out by the Natuna Regency Department of Tourism and Culture in developing geopark tourism support at Geosite Batu Kasah in 2019-2020 has not run optimally, this is due to several factors such as access to Natuna Regency is still difficult and limited, constrained by land acquisition and budget refocussing for the Covid-19 pandemic. Keywords : Government Strategy, Tourism Development, Geopark